Dynamic choice under ambiguity - Marciano Siniscalchi (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
This paper analyzes sophisticated dynamic choice for ambiguity-sensitive decision makers. It characterizes Consistent Planning via axioms on preferences over decision trees. Furthermore, it shows how to elicit conditional preferences from prior preferences. The key axiom is a weakening of Dynamic Consistency, deemed Sophistication. The analysis accommodates arbitrary decision models and updating rules. Hence, the results indicate that (i) ambiguity attitudes, (ii) updating rules, and (iii) sophisticated dynamic choice are mutually orthogonal aspects of preferences. As an example, a characterization of prior-by-prior Bayesian updating and Consistent Planning for arbitrary maxmin-expected utility preferences is presented. The resulting sophisticated MEU preferences are then used to analyze the value of information under ambiguity; a basic trade-off between information acquisition and commitment is highlighted.
Keywords: 330; Entscheidungstheorie; Entscheidungsbaum; Präferenztheorie; Theorie